Conceptual Framework Performance Contributor from Internal Organizations of Corporate Social Responsibility Activities - Handiwibowo, Gogor Arif; Astuti, Rini Puji; Ambarwati, Rita (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
In this 20th century era, the business environment is more demanding that a business organization not only have a profit orientation. However, aspects of the impact on the environment and surrounding communities must also receive adequate attention in line with the increasing quantity and quality of business organizations. The concept of sustainable development is proposed to be a concept that tries to provide a balanced effect between financial performance factors, community welfare factors and environmental sustainability factors. In balancing the three factors above, CSR (Corporate Social Responsibility) activities of business organizations are expected to be the answer to the stigma that business organizations are only looking for profit. This paper will describe several hypotheses as well as a conceptual framework of factors originating from internal business organizations that have an impact on the performance of CSR activities. There are four factors that are proposed to be a hypothesis from the internal organization that must be fulfilled so that CSR activities show their performance. The four factors are fulfilment of human resources, fulfilment of the business organization's strategic vision, fulfilment of operating system implementation, and fulfilment of the business organization's financial capability.